2018
DOI: 10.1111/jvp.12495
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of orbifloxacin in crucian carp (Carassius auratus) after intravenous and intramuscular administration

Abstract: The pharmacokinetics of orbifloxacin was studied after a single dose (7.5 mg/kg) of intravenous or intramuscular administration to crucian carp (Carassius auratus) reared in freshwater at 25°C. Plasma samples were collected from six fish per sampling point. Orbifloxacin concentrations were determined by high-performance liquid chromatography with a 0.02 μg/ml limit of detection, then were subjected to noncompartmental analysis. After intravenous injection, initial concentration of 5.83 μg/ml, apparent eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Crucian carp is one of the most important freshwater fishes cultured in various areas of China, and it is well known for its rapidity in breeding, and convenience in farming, as well as its easy food processing (Yang et al., ). With the rapid development of carp farming in China, the carps are likely to experience some serious infections (Lu et al., ), which have caused huge economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Crucian carp is one of the most important freshwater fishes cultured in various areas of China, and it is well known for its rapidity in breeding, and convenience in farming, as well as its easy food processing (Yang et al., ). With the rapid development of carp farming in China, the carps are likely to experience some serious infections (Lu et al., ), which have caused huge economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Crucian carp is one of the fish species widely cultivated throughout China. It is well‐known for its convenience in farming and rapidity in breeding (Yang et al., ). With the rapid development of carp farming in China, fish are suffering from some serious infections, such as Aeromonas media (Lu et al., ), Rahnella aquatilis (Lu et al., ) and Streptococcus agalactiae (Geng et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Following intramuscular injection, orbifloxacin was absorbed with the absorption rate constant ( K a ). Because of the high bioavailability (96.46%) of orbifloxacin in crucian carp after intramuscular dosing (Yang, Yang, Wang, et al, 2018), it was assumed that all dosed orbifloxacin was absorbed.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that orbifloxacin is safe and effective for treating edwardsiellosis in catfish (Ibrahem et al, 2010) and the infections of Lactococcus garvieae in marine fish (Maki et al, 2008) and A. hydrophila in carp (Li et al, 2008). Our previous studies (Yang, Yang, Wang, et al, 2018; Yang et al, 2019) demonstrated that orbifloxacin was completely absorbed, extensively distributed, and slowly eliminated in crucian carp after intramuscular injection.…”
Section: Introductionmentioning
confidence: 99%